2013
DOI: 10.1063/1.4828475
|View full text |Cite
|
Sign up to set email alerts
|

On the sonic composites without/with defects

Abstract: The sound attenuation in a sonic composite without/with point defects is studied using a new method that combines the features of the cnoidal method and the genetic algorithm. Acoustic scatterers are composed by piezoceramic hollow spheres of functionally graded materials—the Reddy and cosine graded hollow spheres. This method enables to obtain the dispersion relation for defect modes, and the prediction of the evanescent nature of the modes inside the band-gaps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…When no defects into the sonic plate, the frequencies are not affected by variations of the lattice constant, this suggests that they are entirely due to local effects within the individual scatterers [3,4].…”
Section: Resultsmentioning
confidence: 99%
“…When no defects into the sonic plate, the frequencies are not affected by variations of the lattice constant, this suggests that they are entirely due to local effects within the individual scatterers [3,4].…”
Section: Resultsmentioning
confidence: 99%
“…Information theory and its measures play important roles in different areas; the study of wave propagation in different domains (high energy physics, sonoelasticity, signal processing, etc.) requires much information to be processed [9,10]. This Big Data collection often has no practical use unless analyzed effectively to discover qualitative data and meaningful patterns and hierarchies.…”
Section: Introductionmentioning
confidence: 99%
“…The evanescent waves are distributed across the boundary of the waveguide into the surrounding composite. [2][3][4] A review focusing on the fundamental physical aspects of the sonic materials was reported by Miyashita. 5 The sound attenuation band connected to a large acoustic impedance ratio of the matrix and scatterers materials is reported by experimental and theoretical works of Gupta and Ye, 6 S achez-P erez et al, 7 Vasseur et al, 8 Kafesaki and Economou, 9 Psarobas et al, 10 Mart ınez-Sala et al, 11 and Liu et al 12 The plane wave propagation in infinite 2D periodic lattices was investigated by Phani et al 13 using the Floquet-Bloch principles.…”
Section: Introductionmentioning
confidence: 99%